2009
DOI: 10.1128/aem.01910-08
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Single-Nucleotide Primer Extension for Detection and Typing of Phylogenetic Markers Used for Investigation of Microbial Communities

Abstract: Single-nucleotide primer extension (SNuPE) is an emerging tool for parallel detection of DNA sequences of different target microorganisms. The specificity and sensitivity of the SNuPE method were assessed by performing single and multiplex reactions using defined template mixtures of 16S rRNA gene PCR products obtained from pure bacterial cultures. The mismatch discrimination potential of primer extension was investigated by introducing different single and multiple primer-target mismatches. The type and posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…However, a low level of polymerase readthrough can still occur (37), and because PCR results in exponential amplification of a template, even a low level of readthrough can become significant after sufficient PCR cycles. The ability of the Clark primers to amplify B. andersonii and B. americana has already been experimentally identified (26,28), but the B. lonestari result is unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…However, a low level of polymerase readthrough can still occur (37), and because PCR results in exponential amplification of a template, even a low level of readthrough can become significant after sufficient PCR cycles. The ability of the Clark primers to amplify B. andersonii and B. americana has already been experimentally identified (26,28), but the B. lonestari result is unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…sequences obtained from chloroethene‐contaminated groundwater samples. Our recent study demonstrated the excellent specificity of the incorporated labeled nucleotide analogues in SNuPE (Nikolausz et al , 2009b), which is associated with a good dynamic range and the detection of a minority template (Nikolausz et al , 2008).…”
Section: Resultsmentioning
confidence: 96%
“…Blasting of primer pairs for the five tested species against NCBI returned no hits other than the intended targets, meaning that at least one primer of each pair had at least two 3′ or six mismatches to unintended targets. For oral Synergistetes and TM7s, blasting returned unintended targets from some phyla; however, at least either primer had at least one middle and one 3′ mismatch or 3′ nt 1 mismatch to ensure no or, at least, much lower amplification efficiency . In addition, probes also had enough mismatches to compromise detection of non‐specific amplification (Table S1).…”
Section: Resultsmentioning
confidence: 99%